Some Influences of Confucianism on Korean Christian Family Life: Confucian? Christian? Or Confucian-Christian? - Baik, Chung-Hyun 19XX- (Theology today, 2019)
This article investigates some influences of Confucianism on Korean Christian family life, mainly based on Martina Deuchler's highly elaborate sociological research. It examines some characteristics of Choseon society (1392-1910) in contrast to those of Koryeo society (918-1392), thereby enabling us to see more clearly how Confucianism had some influences on Christian family life in Korea, and to determine whether those influences were Confucian, Christian, or Confucian-Christian. In so doing, this article argues that, on the one hand, Korean Christianity has changed and transformed some previous neo-Confucian traditions and customs within family life. On the other hand, however, Korean Christianity might have strengthened, intensified, or at least justified neo-Confucian patrilineal traditions and customs in some areas of family life. Thus now it is time to reexamine the mutual influences and interrelations between Confucianism and Christianity, in order to transmit Christian faith to the next generation in Korea. This task is the more necessary because the Korean church today witnesses a steep decrease of the number of believers and especially of younger believers, and also an increase in the number of so-called "Canaan Believers" in Korea, namely, those who are "believing without belonging," and because such changes are directly or indirectly related to the younger generation's strong antipathy towards Korean Christianity's traces of Confucianism and the patriarchal and hierarchical streams within it.